Estudio de los procesos de control de venta e inventario para el desarrollo de una aplicación web de la Librería “María José” del cantón Montalvo - Rivadeneira Coello, Juan Carlos (2019)
With the present case study which is directly related to the processes of sales control and inventory management; in verifying that it is feasible to implement an inventory control system using a website. Using the research line which is oriented to the development of systems, whose line refers to Software Engineering. In this case study the deductive and inductive methodologies are used in which the deductive is the one that starts from the general to the particular with this proposed topic will be studied and an investigation of the processes of sales control and administration will be carried out. Inventory It is emphasized that in every area it is necessary to optimize resources and that these are automated to obtain greater benefits, that is, from the cost-benefit point of view, it is feasible to develop a SALES AND INVENTORY CONTROL software for the DEVELOPMENT OF A WEB APPLICATION OF THE LIBRARY "MARÍA JOSÉ" DEL CANTÓN MONTALVO ”